Pyrocarbon Interposition Wrist Arthroplasty in the Treatment of Failed Wrist Procedures - Bellemère, Philippe; Maes-Clavier, Catherine; Loubersac, Thierry; Gaisne, Etienne; Kerjean, Yves; Collon, Sylvie (Journal of Wrist Surgery, 2012)
Treatment of failures after prior wrist surgeries with major articular destruction is challenging. In most cases, total wrist fusion is the only possible salvage procedure. We propose a new interposition arthroplasty with a pyrocarbon implant called Amandys.A total of 16 patients, 14 men and 2 women, with a mean age of 56 years were operated on for a failure of wrist surgery performed previously, with an average time lapse of 12 years. The prior surgeries were partial wrist arthrodesis in seven cases, silicone implant interpositions in five cases, advanced Kienböck disease (Lichtman IV) treatment in two cases, proximal row carpectomy in one case, and an isolated scaphoidectomy in one case. A prospective study with clinical and radiological evaluation was performed with a mean follow-up of 24 months (6 to 41 months).Pain and function showed significant improvement. The mean pain score decreased from 7 of 10 to 4 of 10, postoperatively. The mean grip strength was 19 kg (53% of the contralateral side), and the mean range of motion in flexion extension was 68 degrees. Mean strength and range of motion did not change significantly with the operation. The mean QuickDASH (Disability Arm Shoulder and Hand) score decreased from 59 of 100 to 39 of 100. The mean Patient-Rated Wrist Evaluation decreased from 57 of 100 to 33. Two patients (12.5%) required revision for implant repositioning. No dislocation or subsidence of the implant was noted.Pyrocarbon interposition arthroplasty is a new option for treatment of advanced wrist destruction. Preliminary short-term results suggest that it may be a reliable alternative to total wrist fusion. The level of evidence of this study is IV (therapeutic case series).
Keywords: wrist arthroplasty; pyrocarbon implant; wrist osteoarthritis; interposition; failure